Two decades of revolutionizing strategy research: how strategy-as-practice illuminates the complex, dynamic and consequential ways of doing strategy - Jarzabkowski, P; Lê, J; Seidl, D; Vaara, E (Academy of Management, 2024)
Strategy-as-practice (SAP) offers a practice-theoretical perspective on strategy, which is fundamentally different from mainstream strategic management research. This approach has proven especially fruitful in helping us better understand the microlevel processes and practices in strategy work and strategic change challenging many assumptions in mainstream studies. The Academy journals have played a pivotal role in advancing and disseminating SAP research. Therefore, it is now important to summarize and elaborate these contributions by presenting the cumulative insights of SAP as a field of management research. In this introduction, we focus on the key areas of contributions of this body of work, which include (1) identifying the varied and consequential roles and identities of strategic actors, (2) observing the embedded and evolving discursive and sociomaterial practices inherent to strategy work, and (3) challenging the origins, processes and dynamics of strategic change. We use these contributions to draw out opportunities for SAP research to further broaden the set of actors seen as strategists, move beyond the study of single organizations toward studying strategizing on large-scale complex problems, focus more on how issues emerge and become strategic, and recognize the key opportunities and risks in the use of AI and other new technologies in strategy.